The potential of a DIVA-like recombinant vaccine composed by rNcSAG1 and rAtHsp81.2 against vertical transmission in a mouse model of congenital neosporosis - Bengoa Luoni, Sofia Ailin (2019)
Neospora caninum is the etiological agent of neosporosis, a worldwide infectious disease recognized as the major cause of abortions and reproductive failures in livestock, responsible for significant economic losses in cattle industries. Currently, there are not cost-effective control options for this pathology, and the development of a vaccine involving new and integrated approaches is highly recommended. In this study, we evaluated the immunogenic and protective efficacy, as well as the potential DIVA (Differentiation of Infected from Vaccinated Animals) character of a recombinant subunit vaccine composed by the major surface antigen from N. caninum (NcSAG1) and the carrier/adjuvant heat shock protein 81.2 from Arabidopsis thaliana (AtHsp81.2) in a mouse model of congenital neosporosis. BALB/c female mice were intraperitoneal (i.p.) immunized with a mixture of equimolar quantities of rNcSAG1 and rAtHSP81.2 or each protein alone (rNcSAG1 or rAtHsp81.2). The vaccine containing a mixture of rNcSAG1 and rAtHsp81.2 significantly enhanced the production of specific anti-rNcSAG1 total IgG (tIgG), IgG1 and IgG2a antibodies in immunized mice when compared to control groups (non-vaccinated and rAtHsp81.2 immunized mice) as well as to the group of mice immunized only with the antigen (rNcSAG1). In addition, partial protection against vertical transmission and improvement of the offspring survival time was observed in this group. On the other hand, rAtHsp81.2 induced the production of specific anti-rAtHsp81.2 tIgG, allowing us to differentiate vaccinated from infected mice. Despite further experiments have to be made in cattle to test the capability of this vaccine formulation to differentiate vaccinated from infected animals in the field, our results suggest that the formulation composed by rNcSAG1 and rAtHsp81.2 could serve as a basis for the development of a new vaccine approach against bovine neosporosis.